The conjunction between computer algebra and numerical methods - Domarkas, Aleksas; Rakauskas, Rimantas-Jonas; Cicėnas, Silvijus (Lietuvos matematikos rinkinys, 2001)
The report presents the efficiency of using in common Maple and Matlab packages for finding solution (1), which describes the influence of n spherical particles to the external electrostatic field by means of general potential theory.